Dominion of the act vs. Breach of duty in the determination of authority and participation: approach to the intervenor in criminal law in Colombia - Bermúdez Bohórquez, Yonni Albeiro (DIXI, 2024)
The present text arises from the latent indeterminacy of how the participation of the intervenor is being addressed in criminal law. With the entry into force of Law 599 of 2000 (Penal Code), the legislator contemplated a new form of participation in criminal conduct (the intervenor), which appears to fill a normative gap that arose when wanting to penalize individuals who lacked the conditions described in the special criminal type. The method of study is based on the analysis of legal sources and jurisprudence to determine if the theory of the dominion of the fact or the theory of violation of duty manage to present plausible solutions when assigning criminal responsibility. The results show that although the theory of the dominion of the fact enjoys recognition in solving problems of authorship and participation in special crimes, in recent years the theory of violation of duty has gained strength.